PENINGKATAN KESADARAN DAN PENGETAHUAN SISWA MELALUI PELATIHAN PEMASANGAN CCTV - Syaiful Bahri; Maitri Ramadhani; Edi Suprayetno; Ahmad Indra Harahap; Harry Pratama Figna (LPPM STKIP AL MAKSUM, 2023)
This study aims to evaluate the effectiveness of CCTV installation training in increasing students' awareness and knowledge about security. The results showed that the training was effective in increasing students' awareness of school safety and their knowledge of CCTV installation. The long-term impact of this training includes students' active role in maintaining school safety and improving the overall quality of education. Implementation recommendations include comprehensive training planning, collaboration with related parties, evaluation and coaching, as well as further counseling. Although this research has limitations, such as the limited number of samples, the results make an important contribution to the development of innovative and effective learning methods